大迎角机动进气道装置刚柔耦合动力学分析 - 孔鹏; 王克逸; 巫朝君 (Jixie chuandong)
Developing the inlet test installation for with high AOA maneuver the inlet’s characteristics of aircraft in the flight is studied.According to structural features and the motion mode,combining with the theory of flexible,and based on the modal synthesis method,the rigid and flexible coupling model is built inADAMS and hypermesh/optistruct,the dynamic and kinematic characteristics simulation are carried out the dynamics and kinematics characteristics of the rigid-flexible coupling installation are proposed.The results provided the theoretic basis for the development of the inlet test installation for aircraft with high AOA maneuver.